Electrical Engineering: Principles & Applications (Pearson, 2019)
Accessible and applicable learning in electrical engineering for introductory and non-major courses The #1 title in its market, Electrical Engineering: Principles and Applications helps students learn electrical-engineering fundamentals with minimal frustration. Its goals are to present basic concepts in a general setting, to show students how the principles of electrical engineering apply to specific problems in their own fields, and to enhance the overall learning process. This book covers circuit analysis, digital systems, electronics, and electromechanics at a level appropriate for either electrical-engineering students in an introductory course or non-majors in a survey course. A wide variety of pedagogical features stimulate student interest and engender awareness of the material’s relevance to their chosen profession. The only essential prerequisites are basic physics and single-variable calculus. The 7th Edition features technology and content updates throughout the text. Also available with Mastering Engineering Mastering™ Engineering is an online homework, tutorial, and assessment program designed to work with this text to engage students and improve results. Interactive, self-paced tutorials provide individualized coaching to help students stay on track. With a wide range of activities available, students can actively learn, understand, and retain even the most difficult concepts. The text and Mastering Engineering work together to guide students through engineering concepts with a multi-step approach to problems. Note: You are purchasing a standalone product; MyLab™ & Mastering™ does not come packaged with this content. Students, if interested in purchasing this title with MyLab & Mastering, ask your instructor for the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information.